The Urgency of Intensive Mental and Spiritual Development of Civil Servants in Indonesia - Tahir, Rasmiati (Universitas Muslim Indonesia, 2021)
Public services still receive many critics from the community in this country. The pathology of bureaucracy, mal-administration and violation of the code of ethics are still often practiced by civil servant. The purpose of this research was to examine the urgency of mental and spiritual development of civil servant in Indonesia. The method of the research was a combination of literature review and lengthy observations on the process of mental spiritual development in general in various cities in Indonesia. Intensive mental spiritual development of civil servant played an important role to make civil servant to fear to God, to educate their intellectuality, to boost self-competence, and to work totally in their workplace. The conclusion: it was imperative to carry out intensive mental and spiritual development for civil servant at all level of management in the bureaucracy in Indonesia.